Hydrosedimentary records and Holocene environemental dynamics in the Yamé Valley (Mali, Soudano-Sahelian West Africa) - (:unkn) unknown (My University, 2010)
Research conducted in the Yamé Valley (Dogon Country, Mali) provides valuable information about the river systems and their Holocene evolution in Sudano-Sahelian West Africa. Past research in the region has relied primarily on marine and lacustrine records. The new results confirm correlation between palaeoclimatic fluctuations recorded in both the river system and in tropical African lakes. They offer a new continental milestone for understanding of the environmental repercussions of Holocene monsoon oscillations. These studies demonstrate the value of river systems as a palaeoenvironmental record and the role of palaeoclimatic and anthropogenic factors in the Holocene dynamics of Sudano-Sahelian hydrosystems.
Keywords: African Research